The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10555-012-9401-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of the tissue omega-6/omega-3 fatty acid ratio in regulating tumor angiogenesis

Abstract: Angiogenesis is a necessary step in tumor growth and metastasis. It is well established that the metabolites of omega-6 and omega-3 fatty acids, which must be obtained through the diet and cannot be synthesized de novo in mammals, have differential effects on cellular processes. Omega-6 fatty acid (n-6 FA)-derived metabolites promote angiogenesis by increasing growth factor expression whereas omega-3 fatty acids (n-3 FA) have anti-angiogenic and antitumor properties. However, most studies thus far have failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 90 publications
1
44
0
1
Order By: Relevance
“…This is supported by several in vitro studies, where n-3 PUFA administration has been shown to reduce formation of capillary-like structures (tubes) in a number of endothelial cell models (reviewed in Massaro et al (2008)). In vivo evidence is currently limited to tumor-associated angiogenesis, whereby n-3 PUFA administration limits angiogenesis via reduced synthesis of pro-angiogenic AA-derived eicosanoids and transcriptional downregulation of several growth factors (for review see Kang & Lui (2013)). In the placenta, however, n-3 PUFAs appear to promote rather than inhibit vascular development.…”
Section: Omega-3 Fatty Acids and Placental Angiogenesismentioning
confidence: 99%
“…This is supported by several in vitro studies, where n-3 PUFA administration has been shown to reduce formation of capillary-like structures (tubes) in a number of endothelial cell models (reviewed in Massaro et al (2008)). In vivo evidence is currently limited to tumor-associated angiogenesis, whereby n-3 PUFA administration limits angiogenesis via reduced synthesis of pro-angiogenic AA-derived eicosanoids and transcriptional downregulation of several growth factors (for review see Kang & Lui (2013)). In the placenta, however, n-3 PUFAs appear to promote rather than inhibit vascular development.…”
Section: Omega-3 Fatty Acids and Placental Angiogenesismentioning
confidence: 99%
“…The ω-3 LCPUFAs have antithrombotic, antiangiogenic, and anti-inflammatory properties, and they compete with ω-6 LCPUFAs as substrates for synthesis of downstream metabolites by CYP enzymes, cyclooxygenases (COX), and lipoxygenases (LOX) (6,(13)(14)(15). Moreover, dietary enrichment with ω-3 LCPUFAs has been shown to protect against pathological angiogenesis-associated cancer and retinopathy (2,(16)(17)(18)(19). Of the three main pathways (COX, LOX, and CYP) involved in eicosanoid biosynthesis, the lipid mediators derived from the CYP branch are the most susceptible to changes in dietary fatty acid composition (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…The ω-3 double bond that distinguishes DHA and EPA from their ω-6 counterparts provides a preferred epoxidation site for specific CYP family members (20,22). In fact, most CYP isoforms can metabolize EPA and DHA with significantly higher catalytic efficiency than AA, making them uniquely susceptible to variations in the availability of these lipids (19)(20)(21)(22). CYP epoxygenases target the ω-3 double bond, resulting in an accumulation of 17,18-epoxyeicosatetraenoic acid (17,18-EEQ) derived from EPA and 19,20-epoxydocosapentaenoic acid (19,20-…”
mentioning
confidence: 99%
“…Nicastro et al (2012) stated that mutation in Fok1 (polymorphic form of VDR) can cause colorectal cancer. Several authors have reported the importance of PUFA in disease treatment such as angiogenesis related gene expression (VEGF, MMP-2, PDGF) and cell proliferation related gene (PTEN, cyclin, p53, Wnt) that can modulate tumorigenesis (Schmitz and Ecker, 2008;Kang and Liu, 2013). In an investigation, Almendro and Gascon (2012) reported that several minerals have potential role in cancer development.…”
Section: Cancer Treatmentmentioning
confidence: 99%